Development of Oil Palm Lignin-Derived LSG Infused with Nanoadditives for Potential Supercapacitor Application - REMESH, SATHANISWARMAN (IRC, 2021)
In recent days, green components are widely used in industries to increase sustainability and reduce the carbon footprint of a product.